Have India's Financial Market Reforms Changed Firms' Corporate Financing Patterns? - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2002)
Since India embarked on a period of reform, the corporate financial structures have depended on the firms' characteristics. For example, new, small, unprofitable, high-risk firms tend to depend more heavily on domestic loans than old, large, profitable, low-risk firms, as the latter can generate large internal resources. Moreover, the latter have greater access to commercial paper and foreign credit markets compared with the former, suggesting that they can be characterized as high-quality firms. Nevertheless, there are no distinct differences in terms of access to the capital markets among firms. Most bonds are privately placed, which enables even low-quality issuers to raise funds, thanks to loose accounting and disclosure requirements. Moreover, the public equity market has been accessible for a wide range of firms, while it has failed to provide stable sources of finance to firms. This indicates that the informational, legal and judicial infrastructure for an equity market is underdeveloped. Similar conclusions are derived based on the analysis of the characteristics of firms that have more recourse to loans.
hdl:11540/4144
Keywords: 330